Peningkatan Ketahanan Tanaman Pisang Kepok Kuning terhadap Penyakit Darah melalui Variasi Somaklonal dan Simbiosis Endofitik - Arif Wibowo; Tri Joko; Siti Subandiyah; Ika Mariska; Yati Supriyati; Yadi Suryadi; Ika Roostika (Jurnal Perlindungan Tanaman Indonesia, 2010)
One of the obstacles that was encountered in the banana cultivation is blood disease. Blood diseases is caused by Ralstonia solanacearum that is subsequently revised to become blood disease bacteria (BDB). Until now the control of banana blood disease is very difficult. Control of banana blood disease with chemical injections and soil treatment is not effective. This study was aimed to obtain Kepok Kuning cultivar banana seedlings which was resistant towards blood disease obtained from in vitro selection by using BDB growing filtrate and induced resistance by inoculation of antagonistic endophytic bacteria.The observation of Kepok Kuning banana explants treated with various concentrations of BDB growing filtrate showed that the percentage of living explants decreased to 83.33% when the BDB growing filtrate concentration increased to 15%. Treatment of banana explants with BDB growing filtrate also affected the number of roots, shoots, and leaves. Treatment with a single antagonistic endophytic bacteria suppressed the intensity of banana blood disease to 0% in comparison with the mixture of antagonistic endophytic bacteria if Kepok Kuning banana explants were not treated with BDB growing filtrate. When Kepok Kuning banana explants were treated with BDB growing filtrate, the intensity of banana blood disease suppressed to 0% after the high concentration of BDB growing filtrate and the antagonistic endophytic bacteria mixture were applied.